Application of Project Based Learning Model to Improve Learning Outcomes of Grade IV Students in State Elementary School 1 Dukuhmaja - Aprilianti, Velia; Sudrajat, Sudrajat; Eni, Eni (Annpublisher, 2023)
This Research aims for increasing of learn result at second grade SDN 1 Dukuhmaja which has twenty-five students on parts of plants and their functions material with teacher’s effort on planning and doing teaching-learning process using Project Based Learning model. It because of class condition with the problems (1) learn result of Social Sciences was low specifically in parts of plants and their functions material with classical mastery 48,2 %, (2) low of using variation on method and model in teaching, (3) limited for availability of media, tools and infrastructure which support learning process. Based on the research obtains learn result from student’s comprehension in first cycle classical mastery get 65,8% with fifteen students completed and ten students uncompleted. In second cycle, classical mastery reaches 100 % with twenty-five students completed. As for measuring teacher’s skills for planning in first cycle get 3.3 score and 3,8 score in second cycle with really goes category. While for doing teaching learning process in first cycle get 3,5 score and second cycle get 3,8 with really good category. This research projecting in order that implementation of Project Based Learning model in classroom action research should pay attention in each step and increase so many references for used in learning.